(untitled) (Tzintzun, Revista de Estudios Históricos, 2020)
Thousands of Europeans arrived in Latin America during the 19th century to establish themselves as agricultural and industrial workers. In Chile, immigration and colonization were considered as necessary projects for the country’s progress. Thus, the Chilean government organized the establishment of agricultural colonies and promoted industrial immigration to boost the economy. In this sense, this work aims to highlight the importance of the General Agency for Colonization of Chile in Europe, an agency that served as an intermediary between the government and immigrants, and with it, identify the different stages in the Chilean colonization process and the various objectives of official projects.